Serial data transmission at 224 Gbit/s applying directly modulated 850 and 910 nm VCSELs. Issue 19 (20th May 2021) - Ledentsov, N.; Chorchos, Ł.; Makarov, O. Yu.; Shchukin, V. A.; Kalosha, V. P.; Kropp, J.‐R.; Turkiewicz, J. P.; Kottke, C.; Jungnickel, V.; Freund, R.; Ledentsov, N. N.
Abstract: High‐speed discrete multitone serial data transmission over multi‐mode fibre at gross data rates up to 224 Gbit/s achieved with directly modulated oxide‐confined vertical cavity surface emitting lasers at 850 and 910 nm are presented.